The relationship between retinal nerve fiber layer thickness and total retinal blood flow in primary open angle glaucoma. - Flanagan, John G; Yusof, Firdaus; Cheng, Richard; Tayyari, Faryan; Espahbodi, Nadia; Khuu, Lee-Anne; Buys, Yvonne M; Trope, Graham; Hudson, Christopher (2014)
Purpose: To investigate the relationship between Doppler SD-OCT derived retinal blood flow (RBF) and the retinal nerve fiber layer (RNFL) thickness in patients with primary open angle glaucoma (POAG) and healthy age-matched controls. Methods: Thirty three POAG patients (age, 65±8 years; Humphrey Field Analyzer, HFA, mean deviation, MD, -2.28±3.85) and 33 healthy controls (age, 63±5 years; HFA MD -0.48±1.56) were recruited. The Doppler SD-OCT retinal blood flow measurement was taken using the circum-papillary double circular scan protocol in the RTVue system (Optovue Inc., Freemont, CA, USA). A minimum of six RBF scans were acquired. Flow parameters were calculated only from the valid scans. Peri-papillary RNFL thickness was measured using RTVue’s RNFL scan protocol. Results: The total RBF in the POAG group was significantly lower than in the control group (group mean POAG RBF = 30.61±9.29mL/min; group mean control RBF = 40.68±11.32mL/min; p=<0.01). Superior and inferior RBF were also significantly lower in the POAG group (p=<0.01 for both superior & inferior RBF). The average RNFL thickness, superior and inferior RNFL thickness were significantly lower in the POAG group (p=<0.01). Linear regression analysis showed a significant positive correlation between the total RBF and average RNFL thickness (r=0.38, p=0.03), and the superior RBF and superior RNFL thickness (r=0.37, p=0.01). There was no correlation between the inferior RBF and RNFL thickness (r=0.30,p=0.09). Conclusions: There was an association between thinning of the RNFL and reduced inner retinal perfusion in the eyes of patients with POAG.